Combined Effect of Honey, Neem (Azadirachta Indica), and Turmeric against Staphylococcus Aureus and E. Coli Isolated from a Clinical Wound Sample - Saleem, Waqar; Sarfraz, Beenish; Mazhar, Sumaira (BioScientific Review, 2022)
Antimicrobial resistance has become evident all over the world. Resistance to antibiotics has become a concern in case of a wide variety of bacterial species, both pathogenic and commensal. More recently, E. coli, pseudomonas, Staphylococcus aureus, Streptococcus, and Enterococci were found to be adversely affecting the healthcare structures of the world, particularly where acute and long-term care facilities are available. Microbial species were identified by Vitek compact-2 and MALDI-TOF, while antibiogram sensitivity was checked using Kirby Bauer disc diffusion and well diffusion method. The study used 20 wound samples from five (5) men and fifteen (15) women. Thirty-four (34) purified colonies of bacteria were created, in which 8 were E. coli and 2 were S. aureus. The effects of neem, turmeric, and honey with ethanol extracts showed the maximum zone of inhibition against clinically isolated E. coli, such as PM33C4 and AM25C4. While, methanol extract also showed the maximum zone of inhibition against PM56C4, AF34C4, and PM57C4, using disc diffusion and well diffusion methods. Correspondingly, the effect of neem, turmeric, and honey with ethanol extracts showed maximum inhibition against S. aureus. Whereas, methanol extract showed a sensitive zone of inhibition only against PM54C1 using the disc diffusion method. Hence, it was determined that natural ingredients such as honey, turmeric, and neem are an effective alternative to antibiotics because they manifest excellent antimicrobial activity against clinical bacterial isolates.